2017
DOI: 10.1071/cp17307
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the nutriproteomics of chickpea (Cicer arietinum) seeds

Abstract: Chickpea (Cicer arietinum L.) is an essential grain for human consumption owing to its high protein content, nutritional quality and energy-efficient production. The aim of this study was to compare the protein extracts of 24 chickpea genotypes by biochemically characterising the storage proteins. The storage protein content was characterised by protein separation with polyacrylamide gel electrophoresis and visualisation of the banding patterns, which revealed considerable genetic variability within and betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Singh, Shrivastava, Chaturvedi, Sharma, and Bhagyawant () evaluated two chickpea types originating in India (JAKI9218) and USSR (ICC11284) using SDS‐PAGE and found major peptides to be in the range of 10 to 80 kDa. Literature published (Ahmad & Slinkard, ; Ghafoor, Gulbaaz, Afzal, Ashraf, & Arshad, ; Santos et al., ; Shad, Pervez, Zafar, Zia‐Ul‐Haq, & Nawaz, ) on polypeptide profile of different chickpeas did not provide enough data to objectively compare the current study findings.…”
Section: Resultsmentioning
confidence: 76%
“…Singh, Shrivastava, Chaturvedi, Sharma, and Bhagyawant () evaluated two chickpea types originating in India (JAKI9218) and USSR (ICC11284) using SDS‐PAGE and found major peptides to be in the range of 10 to 80 kDa. Literature published (Ahmad & Slinkard, ; Ghafoor, Gulbaaz, Afzal, Ashraf, & Arshad, ; Santos et al., ; Shad, Pervez, Zafar, Zia‐Ul‐Haq, & Nawaz, ) on polypeptide profile of different chickpeas did not provide enough data to objectively compare the current study findings.…”
Section: Resultsmentioning
confidence: 76%
“…In common bean, proteome analysis of common bean deficient in seed storage proteins (phaseolin and lectins) revealed elevated sulfur amino acid content due to increased legumin, albumin 2, and defensin [ 209 ]. Santos et al [ 210 ] characterized the protein content of 24 chickpea genotypes using a proteomics approach to explore genetic variability in storage protein. High-performance liquid chromatography analysis indicated the presence of sufficient genetic variability for SPC, with some genotypes rich in seven amino acids.…”
Section: Proteomics and Metabolomics Shed Light On The Genetic Basis ...mentioning
confidence: 99%
“…Regarding quality, Serrano et al (2017) studied seed and flour characteristics in chickpea and they reported that the chickpea germplasm present a high potential for the improvement of nutritional characteristics. Similarly, Santos et al (2017) also analysed the storage proteins in chickpea using proteomics with a focus in their nutritional aspects.…”
mentioning
confidence: 99%